PENGARUH KONFLIK KEHARUSAN AKUNTABILITAS TERHADAP KINERJA KERJA PEMERINTAH DAERAH - Mesri Welhelmina Nisriani Manafe (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2013)
Accountability of local government have been concern since the issuance of Instruksi Presiden No. 7 Tahun 1999 tentang Laporan Akuntabilitas Kinerja Instansi Pemerintah (LAKIP). In practice, accountability is not running as expected. One indication of the cause of the failure is due to the implementation of accountability. Accountability is seen as an obligation to explain and justify the behavior of accountability actors. The purpose of this study is to empirically examine the relationship between various types of accountability requirement with negative perceived of working context toward accountability actors work performance. This study provides empirical evidence to contribute in the relationship between the various types of requirement accountability and work performance based on institutional theory by using mixed methods, namely quantitative approach using PLS and qualitative approach using semi-structured interviews. The samples in this study were 201 SKPD on NTT local government. The results showed the competing accountability through various types of accountability affect the work context with negative perceived at different levels, but had no effect on accountability actors work performance. Keywords: accountability, accountability requirement, job performance, mixed methods